2022
DOI: 10.29210/020221430
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of waqf planning and development through Islamic financial institutions in Indonesia

Abstract: There is assumption in the community that waqf are physically permanent, and handed over directly to Nazir, even though there are also cash waqf through Islamic financial institutions (IFI). The present research was conducted using a qualitative approach This study aims to analyze the implementation of waqf planning by waqif, waqf development by waqf bodies and the structuring of IFI products in Indonesia related to waqf. This study used a qualitative descriptive method using an online questionnaire to waqif a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In line with Notoadmodjo, (2010) revealed that the development of human resources can be seen from two aspects, namely improving nutrition and increasing non-physical aspects through the accumulation of education and (Soekanto, 2014).…”
Section: Human Resourcesmentioning
confidence: 69%
See 1 more Smart Citation
“…In line with Notoadmodjo, (2010) revealed that the development of human resources can be seen from two aspects, namely improving nutrition and increasing non-physical aspects through the accumulation of education and (Soekanto, 2014).…”
Section: Human Resourcesmentioning
confidence: 69%
“…According to (Sugianto et al, 2022) reveals that community ideas or ideas are the first step in the creation process. The idea runs deliberately and is developed into a work through processing based on observations of the surrounding environment.…”
Section: Community Ideas or Notionsmentioning
confidence: 99%
“…The endowment assurance policy is one of the most sought-after plans (Groll et al, 2022). According to Sugianto et al(2022), premiums are paid for a fixed term, and if the policyholder passes away during the term, the sum assured, along with the accumulated bonus, is paid to the nominee or beneficiary. However, if the policyholder survives the term, they receive the sum assured themselves.…”
Section: Endowment Assurance Policymentioning
confidence: 99%
“…In the context of cash waqf, the involvement of Sharia Financial Institutions (LKS), particularly Cash Waqf Recipient LKS (PWU), is imperative. Islamic insurance is one such institution that has embraced waqf, developing insurance and investment products within Islamic life insurance to bolster growth and capitalize on Islamic insurance in Indonesia (Sugianto et al, 2022;Marsela et al, 2023). However, despite these efforts, there remains a lack of comprehensive understanding and acceptance of waqf, especially cash waqf, among Indonesians, leading to minimal public interest, particularly in regions like North Sumatra.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing interest in waqf and its integration into financial systems, there is a dearth of comprehensive analyses of waqf products in the insurance sector, particularly in Indonesia (Sugianto et al, 2022;Arifin et al, 2022). This research aims to address this gap by examining waqf products for insurance and investment benefits in Islamic life insurance at PT Takaful Keluarga Medan.…”
Section: Introductionmentioning
confidence: 99%